Co-Expression of a Homologous Cytochrome P450 Reductase Is Required for In Vivo Validation of the Tetranychus urticae CYP392A16-Based Abamectin Resistance in Drosophila - Maria Riga; Aris Ilias; John Vontas; Vassilis Douris (Insects, 2020)
Overexpression of the cytochrome P450 monooxygenase CYP392A16 has been previously associated with abamectin resistance using transcriptional analysis in the two-spotted spider mite Tetranychus urticae, an important pest species worldwide; however, this association has not been functionally validated in vivo despite the demonstrated ability of CYP392A16 to metabolize abamectin in vitro. We expressed CYP392A16 in vivo via a Gal4 transcription activator protein/Upstream Activating Sequence (GAL4/UAS) system in Drosophila melanogaster flies, driving expression with detoxification tissue-specific drivers. We demonstrated that CYP392A16 expression confers statistically significant abamectin resistance in toxicity bioassays in Drosophila only when its homologous redox partner, cytochrome P450 reductase (TuCPR), is co-expressed in transgenic flies. Our study shows that the Drosophila model can be further improved, to facilitate the functional analysis of insecticide resistance mechanisms acting alone or in combination.